The crisis of the «gran macchia»: Bigongiari’s Guercino - Daniele Benati (Intrecci d'arte, 2023)
The essay examines the thought of the poet and literary critic Piero Bigongiari (Navacchio, Pisa, 1914 - Florence, 1997) about the path of Guercino. Opposing the traditional reading, which divides it into two distinct phases, Bigongiari maintains its internal coherence in the light of the progressive cooling of the «macchia» (spotlight), an expedient that Guercino had adopted on the example of Ludovico Carracci loading it with an emotional meaning. Drying up, the «macchia» does not lose its expressive potential, but rather is loaded with unreflected and unconscious contents. The example of Guercino serves Bigongiari to critically address the activity of some protagonists of Baroque painting in Florence, to which he dedicated most of his reflections in the artistic field.